Analisis Sentimen Aplikasi Tokocrypto Berdasarkan Ulasan Pada Google Play Store Menggunakan Metode Naïve Bayes - Rizki Adi Saputra; Dion Parisda Ray; Faldy Irwiensyah (STMIK Budi Darma, 2024)
The advancement of increasingly sophisticated technology has brought numerous changes and conveniences for humans in all aspects, including the financial sector. Cryptocurrency has emerged as an innovation in the financial world. A cryptocurrency exchange is an electronic platform that enables sellers and buyers to conduct cryptocurrency trading transactions through a website or mobile application. Currently, many cryptocurrency exchange applications suffer from poor service, unreliable security, lengthy withdrawal processes, high administrative fees, and other issues. As a result, many people in Indonesia rely on reviews on the Google Play Store to check user feedback before deciding to use these cryptocurrency exchange applications. Many Indonesians seek information on cryptocurrency exchange applications that provide the best services for buying and selling cryptocurrency. One such application, according to reviews on the Google Play Store, is Tokocrypto. This study aims to understand the sentiment towards user reviews of the Tokocrypto application using the Naïve Bayes algorithm for data classification. The data obtained consists of 2,000 reviews from the Google Play Store in February 2024, collected using Google Colaboratory. The research stages include data scraping using web scraping techniques, data labeling, preprocessing, TF-IDF weighting, implementing the Naïve Bayes algorithm, and evaluation. The cleaned data resulted in 1,000 reviews, with 396 positive sentiments and 604 negative sentiments. The results of sentiment analysis research using the Naïve Bayes algorithm method show 74.22% for accuracy, 63.25% for precision, and 81.40% for recall.